Impact of biliary stents in the performance of the EUS-guided tissue acquisition: A systematic review and meta-analysis - Guzmán-Calderón, Edson (2023)
Introduction and aim: Pancreatobiliary tumours are challenging to diagnose exclusively by imaging methods. Although the optimum moment for carrying out the EUS is not well defined, it has been suggested that the presence of biliary stents may interfere with the proper staging of tumours and the acquisition of samples. We performed a meta-analysis to evaluate the impact of biliary stents on EUS-guided tissue acquisition yield. Material and methods: We conducted a systematic review in different databases, such as PubMed, Cochrane, Medline, and OVID Database. A search was made of all studies published up to February 2022. Results: Eight studies were analyzed. A total of 3185 patients were included. The mean age was 66.9 ± 2.7 years; 55.4% were male gender. Overall, 1761 patients (55.3%) underwent EUS guided tissue acquisition (EUS-TA) with stents in situ, whereas 1424 patients (44.7%) underwent EUS-TA without stents. The technical success was similar in both groups (EUS-TA with stents: 88% vs EUS-TA without stents: 88%, OR = 0.92 [95% CI 0.55–1.56]). The type of stent, the needle size and the number of the passes were similar in both groups. Conclusions: EUS-TA has similar diagnostic performance and technical success in patients with or without stents. The type of stent (SEMS or plastic) does not seem to influence the diagnostic performance of EUS-TA. Future prospectives and RCT studies are needed to strengthen these conclusions.